Implementasi Model Pintar Untuk Meningkatkan Aktivitas, Keterampilan Memecahkan Masalah Dan Hasil Belajar Siswa Muatan Matematika Di Kelas IV Sekolah Dasar - Rahmawati; Aslamiah (CV. ITTC INDONESIA, 2023)
The problem in this study is that learning is only one-way and less attractive to students resulting in low activity, problem-solving skills and student learning outcomes that do not meet the specified Minimum Completeness Category (KKM) standard of 75. The purpose of this study is to describe teacher activities and analyze student activity problem solving skills and learning outcomes using the PINTAR model. The approach used is a qualitative approach with the type of Classroom Action Research (PTK) which is carried out in 3 meetings. The research subjects were fourth grade students at SDN Alalak Selatan 2 for the academic year 2022/2023, with a total of 22 students. The results showed: (1) teacher activity scored 34 very good categories, (2) student activity reached the very active category of 96%, (3) problem solving skills 86% and (4) classical mastery of student learning outcomes in cognitive, affective, and psychomotor (skills) by 100%. Based on the results of the study it can be concluded that activity, problem solving skills and student learning outcomes in mathematics content in the material of presenting data with bar charts using a combination of the PINTAR model in Class IV elementary schools have increased.